A novel contextual topic model for multi-document summarization. Issue 3 (15th February 2015) - Yang, Guangbing; Wen, Dunwei; Kinshuk; Chen, Nian-Shing; Sutinen, Erkki
Highlights A novel contextual topic model is proposed for multi-document summarization. The main idea is to leverage hierarchical topics and their correlations with respect to the lexical co-occurrences of words. The proposed contextual topic model can effectively determine the relevance of sentences.